2020
DOI: 10.32725/jab.2020.016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Rosmarinus officinalis L. essential oil and its nanoemulsion on dyslipidemic Wistar rats

Abstract: Dyslipidemias are lipid metabolism alterations that cause increased levels of serum lipoprotein, cholesterol, and triglycerides. These alterations are associated with a higher incidence of cardiovascular diseases and are a risk factor for atherosclerosis development. This study aimed to evaluate the effect of Rosmarinus officinalis essential oil (EORO, 100 mg/kg) and its nanoemulsion (NEORO, 500 µg/kg) on Triton and coconut saturated-fat-induced (CSF) dyslipidemias using Wistar rats. The phytochemical evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Furthermore, R. officinalis has long been used as a medicinal plant. In this context, a plethora of biological effects and health benefits have been attributed to rosemary essential oil, leaf extracts, and isolated substances, including antibacterial [ 16 , 17 , 18 ], antifungal [ 19 , 20 ], anti-inflammatory [ 21 , 22 ], antiatherogenic [ 23 , 24 ], antiangiogenic [ 25 , 26 ], antihypertensive [ 27 ], antiulcer [ 28 ], anti-diabetic [ 29 , 30 ], anticancer [ 31 ], and other effects (reviewed elsewhere [ 32 , 33 ]). In addition to these effects, this plant is also well known for its powerful antioxidant activity (reviewed in [ 34 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, R. officinalis has long been used as a medicinal plant. In this context, a plethora of biological effects and health benefits have been attributed to rosemary essential oil, leaf extracts, and isolated substances, including antibacterial [ 16 , 17 , 18 ], antifungal [ 19 , 20 ], anti-inflammatory [ 21 , 22 ], antiatherogenic [ 23 , 24 ], antiangiogenic [ 25 , 26 ], antihypertensive [ 27 ], antiulcer [ 28 ], anti-diabetic [ 29 , 30 ], anticancer [ 31 ], and other effects (reviewed elsewhere [ 32 , 33 ]). In addition to these effects, this plant is also well known for its powerful antioxidant activity (reviewed in [ 34 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, rosemary extracts have shown promising potential in the development of antidiabetic drugs (Quirarte‐Baez et al., 2019; Yun et al., 2021). The antidiabetic effects of rosemary include the inhibition of advanced glycation end products (AGEs) produced by glycosylation (Shen et al., 2020), suppression of glycogenesis (Bao et al., 2020), promotion of insulin synthesis and glucose uptake (Lipina & Hundal, 2014; Naimi et al., 2015), enhancement of fat consumption (Razavi et al., 2020), anti‐inflammatory (Bao et al., 2020), antioxidant (Abdelrahman et al., 2020; Selmi et al., 2017), lowering blood lipids (El‐Beeh et al., 2019; Hassani et al., 2016), as well as anti‐atherosclerosis (Rodrigues et al., 2020). These antidiabetic pharmacological effects might be attributed to the excellent regulatory functions of multiple enzymes, different signal transduction pathways, transcription factors, and key gene expressions (Hassani et al., 2016).…”
Section: Biological Activities Of Rosemary Extractmentioning
confidence: 99%
“…Zaouali and Boussaid (2008) found that essential oil extracted from Rosmarinus officinalis was rich in 1,8-cineol, while Moujahed et al (2011) found that Rosmarinus officinalis was contained 0.43% essential oil that fractionated into 1-8 cineol (44.2%), camphor (12%), -pinen (11.6%), Camphen (4%), -thyjen (2.2%) and -terpineol (1.7%). In more specifically, Rodrigues et al (2020) reported that the chromatography analysis showed 100% of terpenes in essential oils of rosemary composition with extra 20 compounds could be identified as α-pinene (8.13%), limonene (21.99%), 1,8cineole (33.70), and camphor (27.68%). α-thujene (0.11%), Camphene (1.68%), α-terpinene (0.45) and γterpinene (0.39) where these values being similar with those reporting by (Fernandes et al, 2013 andBorges et al, 2017).…”
Section: Essential Oil and Active Constituentsmentioning
confidence: 99%
“…Extra explanation for reducing cholesterol and triglycerides is representing in stimulating the conversion of cholesterol to bile acids which are excreted from the body through the enterohepatic circulation (Jun et al, 2012 andHu et al, 2015). Definitly Rodrigues et al (2020) reported that each of 100 mg/kg essential oil from rosemary (EORO) could significantly reduce the levels of total cholesterol, triglycerides, and LDL. Consistent with these findings, Aser and AL-Abachi (2021) showed that after 4 weeks of treating rats by 250 mg\kg body weight of bay leave extracts, there was significant decreases in fasting blood glucose, triglyceride, total cholesterol, LDL, VLDL, ALT, AST, alkaline phosphatase, and a significant increases in HDL and body weights.…”
Section: Blood Parametersmentioning
confidence: 99%